Domestic violence in South Australia: a population survey of males and females - Eleonora Dal Grande; Jacqueline Hickling; Anne Taylor; Tony Woollacott (Elsevier, 2003)
Abstract Objective: To determine the self‐reported prevalence of domestic violence in South Australian adults and to examine the associated risk factors, demographic factors and related health issues using computer‐aided telephone interviewing (CATI) methodology. Sample: A representative random sample of South Australian adults aged 18 years and over selected from the Electronic White Pages. Overall, 6,004 interviews were completed (73.1% response rate). Results: In total, 17.8% of adults in South Australia reported some form of domestic violence by a current or an ex‐partner. Demographic factors such as low household income, unemployment or part‐time employment and health variables such as poor to fair self‐reported health status and alcohol abuse problems were found to have a significant relationship with domestic violence. Conclusions: Approximately one in five South Australian adults report physical and emotional abuse from current or ex‐partners, of whom the majority are women who are separated, divorced or never married and on lower incomes. Telephone interviewing is a cost‐effective method of identifying prevalence estimates of domestic violence when compared with data collection by way of police reports or hospital emergency statistics. Implications: Domestic violence is a serious public health concern often 'hidden' by the lack of appropriate data. This study has shown that domestic violence is frequent and has important social, economic and health consequences.